Covid-19 Pandemic and Its Effects on Social Life and Reflections on Spatial Preferences (International Journal of Built Environment and Sustainability, 2022)
The Covid-19 pandemic, which emerged in Wuhan city of China's Hubei province in December 2019, affected the whole world in a short period of 3 months. The Covid-19 outbreak, which was declared a pandemic by the World Health Organization as of March 12, 2020; was imposed significant restrictions on the use of open spaces, which adversely affected the daily life of individuals physically, mentally and socially. Apart from the health problems experienced by people, it has also created many spatial choices and changes. New preferences, where social distance is at the forefront, have started new venue organizations along with new requests. Although the changes experienced with the Covid-19 pandemic may seem negative, they contain opportunities that allow change and development. Making people's living environments more functional, remembering the importance of nature and reviewing social relations can be evaluated in this context. Looking from history to the present, the Covid-19 pandemic is not the first and will not be the last. For this reason, the study aims to investigate the change in the spatial preferences in the society with the pandemic and to create an idea for the next pandemics. In this context, 289 people were reached by using the online survey method and various questions were asked. Various results were obtained and interpreted by performing variance analysis, factor analysis, correlation analysis, crosstabs test and frequency analysis (P˂0.01) on the obtained data. As a result of the study, from the statistical data, it has been observed that 'people are more oriented to nature' due to the Covid-19 pandemic and that open green spaces suitable for social distance are sought in spatial preferences. These findings shed new light on the value of urban nature as resilience infrastructure during a time of crisis.
Keywords: Environmental problems, human-nature relationship, landscape design in Covid19